Fifteen years of experience with the oral live-attenuated human rotavirus vaccine: reflections on lessons learned. (2nd August 2020) - Pereira, Priya; Vetter, Volker; Standaert, Baudouin; Benninghoff, Bernd
ABSTRACT: Introduction: Rotavirus (RV) disease remains a prominent cause of disease burden in children <5 years of age worldwide. However, implementation of RV vaccination has led to significant reductions in RV mortality, compared to the pre-vaccination era. This review presents 15 years of real-world experience with the oral live-attenuated human RV vaccine (HRV; Rotarix ). HRV is currently introduced in ≥80 national immunization programs (NIPs), as 2 doses starting from 6 weeks of age. Areas covered: The clinical development of HRV and post-marketing experience indicating the impact of HRV vaccination on RV disease was reviewed. Expert opinion: In clinical trials, HRV displayed an acceptable safety profile and efficacy against RV-gastroenteritis, providing broad protection against heterotypic RV strains by reducing the consequences of severe RV disease in infants. Real-world evidence shows substantial, rapid reduction in the number of RV infections and associated hospitalizations following introduction of HRV in NIPs, regardless of economic setting. Indirect effects against RV disease are also observed, such as herd protection, decrease in nosocomial infections incidence, and a reduction of disease-related societal/healthcare costs. However, not all countries have implemented RV vaccination. Coverage remains suboptimal and should be improved to maximize the benefits of RV vaccination. PLAIN LANGUAGE SUMMARY: What is the context? Rotaviruses are a leading cause of diarrheal diseases worldwide. They account for substantial morbidity and mortality among young children under 5 years, with developing countries showing a higher disease burden. Although rotavirus vaccines have contributed to reductions in disease burden, they have not substantially averted deaths from rotavirus infection in the regions with the highest burden due to low coverage What is new? We reviewed almost 15 years of data from national immunization programs and private use settings to summarize the global experience with the rotavirus vaccine Rotarix (GSK). We showed that vaccination with Rotarix : Has a long term and substantial impact on disease burden in diverse geographic and socio-economic settings Significantly reduces diarrhea-related hospitalizations and death rates Provides indirect benefits such as herd protection to children who are too old or too young to be vaccinated; the reduction of hospital-acquired infections; and significant cost savings for healthcare systems, households and society. Why is this important? Despite promising real-world data and a favorable benefit-risk profile, the overall uptake of Rotarix is still suboptimal Increasing awareness of the high disease burden and significant vaccine impact is critical for motivating healthcare professionals to advocate for rotavirus vaccination and convincing policymakers to implement national rotavirus immunization